2019
DOI: 10.1002/cne.24825
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog expression in zebrafish forebrain identifies the teleostean pallidal signaling center and shows preglomerular complex and posterior tubercular dopamine cells to arise from shh cells

Abstract: Ventralization, a major patterning process in the developing vertebrate neural tube (central nervous system, CNS), depends on Sonic hedgehog (SHH) as a main signaling morphogen. We studied the CNS of late larval and young adult zebrafish in a transgenic shh‐GFP line revealing increased neuroanatomical detail due to the progressed differentiation state compared to earlier stages. Some major findings emerge from the present study. (a) shh –GFP is still expressed along the adult zebrafish CNS neuraxis in most loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 165 publications
(301 reference statements)
8
44
0
Order By: Relevance
“…(1) Most of the subpallial amygdaloid nuclei in zebrafish (CeAa, CeAl, BSTa, BSTp, and MeAd) form part of the GABAergic, isl1:GFP-free region that we propose corresponds to or develop within the region of the dorsal lateral ganglionic eminence (dLGE); not to the "dorsal striatum" as previously suggested (Ganz et al, 2012). The isl1:GFP positive BSTm represents an extension of the striatopallidal systems, that is the teleostean counterpart of the tetrapod medial ganglionic eminence (MGE) that gives rise to the pallidum consistent with a former study that identified this nucleus (Ganz et al, 2012) as well as a study that confirmed its pallidal identity (Wullimann and Umeasalugo, 2020). In contrast, we interpret the newly identified MeAv, despite its absence of isl1-driven GFP, as an extension of the striatum proper based on the presence of both substance P and calretinin cells (this study).…”
Section: Overviewsupporting
confidence: 89%
“…(1) Most of the subpallial amygdaloid nuclei in zebrafish (CeAa, CeAl, BSTa, BSTp, and MeAd) form part of the GABAergic, isl1:GFP-free region that we propose corresponds to or develop within the region of the dorsal lateral ganglionic eminence (dLGE); not to the "dorsal striatum" as previously suggested (Ganz et al, 2012). The isl1:GFP positive BSTm represents an extension of the striatopallidal systems, that is the teleostean counterpart of the tetrapod medial ganglionic eminence (MGE) that gives rise to the pallidum consistent with a former study that identified this nucleus (Ganz et al, 2012) as well as a study that confirmed its pallidal identity (Wullimann and Umeasalugo, 2020). In contrast, we interpret the newly identified MeAv, despite its absence of isl1-driven GFP, as an extension of the striatum proper based on the presence of both substance P and calretinin cells (this study).…”
Section: Overviewsupporting
confidence: 89%
“…The teleostean posterior tubercle has remained enigmatic historically because of its relatively small amniote counterpart. However, recent basic Helix–Loop–Helix (bHLH) gene expression studies in amniotes (Osório, Mueller, Rétaux, Vernier, & Wullimann, 2010) and zebrafish (Mueller & Wullimann, 2016), as well as comparative developmental studies on dopamine cells in the basal midbrain (where dopamine cells are absent in teleosts; Meek, 1994) and diencephalon (where dopamine cells are present in all vertebrates; see Vernier & Wullimann, 2009 and Wullimann & Umeasalugo, 2019, for reviews) identified these basal diencephalic regions in all vertebrates (generally called bP1 through bP3 as shown for amniotes in Figure 1a, or N, PTd, and PTv in anamniotes; see below for more details).…”
Section: The Posterior Tuberculum and Preglomerular Complex: An Enlarmentioning
confidence: 99%
“…All basal divisions of midbrain (T, midbrain tegmentum, Figure 1), as well as of diencephalic bP1 through bP3, show different gene expression compared to their alar complements (Osório et al, 2010). These mesodiencephalic basal regions contain dopamine cells in amniotes and amphibians, or cartilaginous fish for that matter (reviewed in González & Smeets, 1994; Smeets & González, 2000; Smeets & Reiner, 1994a, 1994b; Vernier & Wullimann, 2009; Wullimann, 2014; Wullimann & Umeasalugo, 2019). However, in teleosts the dopamine cells of this multiprosomeric basal mesodiencephalic region are restricted to the posterior tuberculum.…”
Section: The Posterior Tuberculum and Preglomerular Complex: An Enlarmentioning
confidence: 99%
“…At early embryonic stages (before 30 hpf) in both quadruple transgenic lines, the Cre expression appears to extend from dorsal to ventral MHB, therefore it is hard to conclude whether the PG cells derive from the alar or basal portion. A recent publication using shh -GFP transgenic line suggests that the adult PG contains shh -expressing cells (GFP+ in the transgenic line), indicating that some PG cells may be of basal origin ( Wullimann and Umeasalugo, 2020 ). In contrast, the expression of Cre at later stages (after 48 hpf) is limited to the alar portion of the mesencephalon (notably tectal area).…”
Section: Discussionmentioning
confidence: 99%